Attaining effective and speedy resolutions of unfair dismissal disputes in Lesotho: An explorarion of possible lessons from South Africa - Ntaitsane, Mamolefi Anacletta (National University of Lesotho, 2023)
National Manpower Development Secretariat
Keywords: Labour dispute; Lesotho; Resolution mechanisms; Unfair dismissal disputes

Structural Change, Productivity Growth and Labour Market Turbulence in Sub-Saharan Africa - Mensah, Emmanuel; Owusu, Solomon; Foster-McGregor, Neil; Szirmai, Adam (Journal of African Economies, 2023)
This paper presents a shift-share decomposition of the role of structural change in driving labour productivity in sub-Saharan Africa (SSA). The paper further examines the effect that the observed structural change has had upon the dynamics of labour markets in SSA. The analysis is based on a newly constructed dataset, the Extended Africa Sector Database. This database updates and extends the Africa Sector Database of the Groningen Growth and Development Centre. It includes eighteen countries covering the period 1960–2015. Overall, the database shows that productivity growth has been slow, with large and persistent sectoral productivity gaps present. The extent of structural change has been higher than that observed in previous studies, however. But while the share of employment and value added in agriculture has declined, resources have been pulled into certain service sectors that have relatively low productivity, thus limiting aggregate productivity improvements. The general direction of structural change has not been towards the most productive sectors. Results of the labour market analysis complement this analysis, providing suggestive evidence of a role for labour market institutional arrangements in many SSA countries in affecting these outcomes.

Exploring the Voice of Populist Movements in the Employment of Foreign Nationals: A Comparative Study of Botswana and South Africa - Utete, Reward; Zhou, Sheunesu; Ajani, Oluwatoyin Ayodele (International Journal of Social Science Research and Review, 2023)
Labour immigration has been on the rise and has had policy implications for public leaders of relatively stable Southern African Development Corporation (SADC) countries. In this paper, the status of populism and labour immigration in Botswana and South Africa was explored. The primary sources of labour immigration are Zimbabwe and Mozambique. Economic disparities and the disintegration of the socio-economic conditions of the neighbouring countries have been major antecedents for the labour movements of the masses. The study utilised a qualitative method and comparative case study design. The study found that populist movements have much influence on the termination of employment of foreign nationals in Botswana and South Africa as shown by their anti-immigrant attitudes, market protectionism, and close-the-borders protests. As these measures have become inefficient over the years, policies and proposals are recommended in response.
Keywords: Economy; Employment; Foreign Nationals; Immigrants; Policies; Populist Movements

The legal regulation of trade union recognition in South Africa in historical and comparative context - Germishuys-Burchell, Wilhelmina (Stellenbosch University, 2023)
This study investigates the impact and importance of the legal regulation of trade union recognition and associated challenges in South Africa. It evaluates the current regulation of trade union recognition, including legislation and judicial attitudes apparent from the interpretation, application, and enforcement of such legislation, to ascertain its continued appropriateness in the current South African industrial relations environment. The study considers the policy choices of both voluntarism and majoritarianism underlying the Labour Relations Act 66 of 1995 (“LRA”) and the “workplace” constituency to which it applies as factors that might be contributing to challenges experienced in the current regulation of collective bargaining in South Africa. It evaluates the current model of trade union recognition and representativeness as it applies to the acquisition by trade unions of organisational rights, collective bargaining rights and trade union recognition for purposes of retrenchment consultation. It recognises that the specific model chosen to regulate the representative status of trade unions has a significant effect on the ability of trade unions to organise and conclude collective agreements and, as such, on the distributive effects of such agreements in the labour market and broader society. The study commences with an historical overview of the regulation of trade union recognition under the 1956 LRA and thereafter considers the 1995 LRA as a product of criticism against the 1956 LRA. Specific issues considered, largely based on the analysis of the relevant decisions by the Constitutional Court, include the following: the impact of Constitutional Court jurisprudence relating to trade union recognition on the process of collective bargaining and on the legal regulation of the right to strike; the role of representativeness and its link with the workplace as the constituency for recognition and acquisition of organisational rights; the often winner-takes-all effect of the current model on collective bargaining as a major cause of labour unrest; the reactive role the legislature has played over the past, almost three decades to address challenges; the extent to which intervention should take place to safeguard the institution of collective bargaining from being undermined as well as the regulation of collective agreements as the product of collective bargaining and as the primary source of terms and conditions of employment. The comparative review of Canadian law focuses on a number of issues selected specifically for their potential to provide insights into how the weaknesses in South African regulation may be remedied. This includes insights into the accommodation of special or significant minority interests and how to address recognition in the context of multi-location employers. The thesis concludes with remarks on the insights gained from the Canadian model and the 1956 LRA. Where appropriate, suggestions are made on the way forward for South Africa as to the appropriate regulation of trade union recognition and representativeness.
Keywords: Collective bargaining; Collective labor agreements; Dismissal of employees; Employee rights; Industrial laws and legislation; Labor disputes; Labor unions; South Africa

Effective strategies for resolving labour disputes in the corporate sector: Lessons from Nigeria and the United States - Uzougbo, Ngozi Samuel; Akagha, Onyinyechi Vivian; Coker, Julie Olajumoke; Bakare, Seun Solomon; Ijiga, Amina Catherine (World Journal of Advanced Research and Reviews, 2023)
The relationship between an employer and employee though governed by various laws and regulations can still at some point witness some disagreements and dispute. Labour disputes are not uncommon neither are they peculiar to a particular industry in a country. Usually, trade disputes are hinged on agitation of employees for compensation, good working conditions, job stability and agitation against unlawful termination or dismissal of from service. Over the years, employees have adopted different ways to exhibit their discomfort and grievances in order to convey their message such as strike actions, peaceful protest and so on.  There’s no doubt that these disputes will drastically reduce the level of productivity and overall beneficial impact of the industries in the economic growth of the country. Hence, there’s a need to adopt strategies for resolving these labour disputes. Some industries have applied round table discussions, arbitration, mediation, collective bargaining as well as grievances remedial processes. This work will provide an overview of the causes of disputes in the corporate sector, examine the features of the Nigerian and United States disputes resolution system and also juxtapose the strategies for resolving labour disputes in the two countries. Furthermore, it will provide recommendations to effectively addressing labour issues within the business sector.
Keywords: ADR; Alternative dispute resolution; Industrial relations; Legislative Framework; Multi-door courthouse; Trade unions